City of screens imagining audiences in Manila's alternative film culture - Trice, Jasmine Nadua (Duke University Press, 2021)
"In City of Screens, Jasmine Nadua Trice examines the circulation of local and transnational alternative cinemas in early-2000s Metro Manila, Philippines. Trice considers how these circulations took shape in the wake of digital media piracy, the decline of the once-prolific, local commercial film industry, and the rise of an independent cinema movement heralded as a new national cinema both within the Philippines and abroad. The book focuses on sites of exhibition and distribution, including the pirated DVD district, the mall multiplex, and arthouse cinemas"--